Estudio de la actividad fotocatalítica de películas de poli 3,4-Etilendioxitiofeno depositadas por Electropolimerización (2016)
This document gives the information about how to replicate electropolymerization process in a potentiostat Brand bioanalytical systems CV-50W control dipositive who hips to a maintain constant the potential between the working electrode and the reference electrode in a electromechanically cell, and drawing the cyclic colt grams showing the relation of the potential and the current in the electrodeposition of the edit in into glass.